Antiviral Effects and Mechanisms of Action of Water Extracts and Polysaccharides of Microalgae and Cyanobacteria - Besednova, Natalya N.; Andryukov, Boris G.; Kuznetsova, Tatyana A.; Zaporozhets, Tatyana S.; Kryzhanovsky, Sergey P.; Ermakova, Svetlana P.; Shchelkanov, Mikhail Yu. (Journal of Pharmacy and Nutrition Sciences, 2022)
Microalgae (MA) and cyanobacteria (CB) are currently attracting much attention from scientists due to the high biological activity of many secondary metabolites of these aquatic organisms. This review presents up-to-date modern data on the prospects for using polysaccharides (PS) of these marine aquatic organisms as effective and practically safe antiviral agents. These natural biopolymers are polyvalent compounds, which allows them to bind to several complementary biological target receptors. Particular emphasis is placed on the exopolysaccharides (EPS) Spirulina sp. (Arthrospira sp.), Porphyridium sp., Chlorella sp., and Euglena sp., whose antiviral activity makes them promising for the creation of drugs, biologically active food supplements, and products for functional nutrition. The mechanisms of the biological action of PS and the targets of these compounds are presented with a brief description of PS’s anti-inflammatory, immunomodulatory and antioxidant actions, which make the most significant contribution to the antiviral effects. The authors hope to draw the attention of researchers to the use of water extracts and polysaccharides of microalgae and cyanobacteria as potential broad-spectrum antiviral agents that can become the basis for new antivirus strategies.